1998
DOI: 10.1161/01.cir.98.7.663
|View full text |Cite|
|
Sign up to set email alerts
|

Adverse Events With Transvenous Implantable Cardioverter-Defibrillators

Abstract: on behalf of the European 7219 Jewel ICD InvestigatorsBackground-A newly developed classification system relates adverse events to the surgical procedure or the function of the implantable defibrillator. Methods and Results-Adverse events were monitored during prospective clinical evaluation of the Medtronic model 7219Jewel ICD and were classified according to the definitions of the ISO 14155 standard for device clinical trials into 3 groups: severe and mild device-related and severe non-device-related adverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
82
2
5

Year Published

2000
2000
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 215 publications
(96 citation statements)
references
References 31 publications
(26 reference statements)
7
82
2
5
Order By: Relevance
“…With the advent and then dominance of primary prevention indications, avoidable shocks assumed a relatively larger proportion of total therapy [78][79][80][81][82][83]. Gradually, publications have increased awareness of the frequency and the diverse range of adverse outcomes associated with avoidable ICD therapy, and have demonstrated that avoidable ICD shocks can be reduced by evidence-based programming of the detection rate, detection duration, antitachycardia pacing (ATP), algorithms that discriminate supraventricular tachycardia (SVT) from VT, and specific programming to minimize the sensing of noise [81][82][83][84][85][86][87][88][89][90][91][92].…”
Section: Tachycardia Detection Programmingmentioning
confidence: 99%
“…With the advent and then dominance of primary prevention indications, avoidable shocks assumed a relatively larger proportion of total therapy [78][79][80][81][82][83]. Gradually, publications have increased awareness of the frequency and the diverse range of adverse outcomes associated with avoidable ICD therapy, and have demonstrated that avoidable ICD shocks can be reduced by evidence-based programming of the detection rate, detection duration, antitachycardia pacing (ATP), algorithms that discriminate supraventricular tachycardia (SVT) from VT, and specific programming to minimize the sensing of noise [81][82][83][84][85][86][87][88][89][90][91][92].…”
Section: Tachycardia Detection Programmingmentioning
confidence: 99%
“…Approximately one-third of patients will experience some adverse effect, including inappropriate shocks, lead problems, and infection. 4,5 The implantation and testing procedure occasionally precipitates hemodynamic deterioration. 6 DDD or VVI pacing from the right ventricular lead of the ICD may have adverse hemodynamic effects, including increasing dyssynchrony of left ventricular contraction, and may have contributed to the aggravation of heart failure observed in the Multicenter Automatic Defibrillator Implantation Trial II (MADIT II).…”
mentioning
confidence: 99%
“…1,2 Tachycardia is identified primarily from the measurement of heart rate and/or the morphology of an intraventricular electrogram, so ICD therapy can be prescribed for supraventricular tachycardia or other causes of increased heart rate. [3][4][5] However, for supraventricular tachycardia, a dual-chamber ICD would decrease the frequency of inappropriate shocks from the ICD. Other mechanisms of inappropriate discharge of the ICD include non-sustained VT, pacemaker interference or T-wave oversensing.…”
mentioning
confidence: 99%